Nutzungsreserven und -potenziale für die Siedlungsentwicklung nach innen. Eine Auslegeordnung und aktuelle Forschungsprojekte in der Schweiz. - Grams, Anita; Nebel, Reto (Routledge, 2013)
Ziel des Artikels ist es, Aspekte der konkreten Umsetzung der Strategie Innenentwicklung vor Außenentwicklung in der Schweiz aufzuzeigen und den damit verknüpften weiteren Forschungsbedarf zu identifizieren. Als empirische Basis dienen Ergebnisse aus aktuellen Raum-Kooperationsprojekten sowie aus einem durch den Schweizerischen Nationalfonds geförderten Forschungsprojekt.

Switzerland has a limited supply of suitable settlement land and in future must put a stronger focus on existing settlement areas for its spatial development. The corresponding strategy "redevelopment before new development" must find its realization through an increase in the level of use and a simultaneous improvement of the spatial quality in extensively built-up settlement areas. This can take place within the space planned by the building and planning laws in force (mobilization of land-use reserves), or, areas can be identified that are appropriate for a local -increase of land use measures valid at this time (mobilization of land-use potential). A precondition for consistent settlement redevelopment is a problem-oriented overview of the available reserves--and land-use potential. Methods to achieve systematic recognition, mobilization, and implementation for these two categories have been little researched. While land-use reserves could be quantitatively and qualitatively identified and recorded through an approach developed at ETH Zurich, the identification of land-use potential has not advanced as far. Test planning procedures will be used to check what potential is available and whether it can make a useful contribution to redevelopment. The design of appropriate processes and procedures in professional daily life and in the education of planners should be placed at the forefront.
Land-use reserves and the potential for settlement development through redevelopment: An overview of current research projects in Switzerland.
Keywords: Raumplanung; Siedlungsstruktur; Stadtentwicklung; Siedlungsentwicklung; Stadtwachstum; Urbanität; Innenstadt; Stadtrand; Forschungsprogramm; Forschungsprojekt; Planungsrecht; Flächennutzung; Reurbanisierung; Innenentwicklung; Nutzungspotenzial; Reservefläche